Influence of cooling and frequency of repair of the pusher furnace isolation on heat consumption - V. Blagodarnyj; P. Horbaj; I. Andrejchak (Литьë и металлургия)
There are examined the factors, influencing on the efficiency of the pusher furnace operating in respect to reduction of heat loss.